HUMAN TRAFFICKING IS A THREAT AGAINST HUMANITY (TAMADDUN NURI JURNALI, 2024)
In the modern era of globalization, human trafficking is one of the pressing problems that attracts the attention of the entire world community. The article makes an attempt to reveal such issues that human trafficking is an illegal crime, its cases have also been identified in Uzbekistan, and the need to take measures to prevent this crime.